Efisiensi Manajemen Kas dan Dampaknya terhadap Profitabilitas Perusahaan di Sektor Perdagangan Ritel di Indonesia - Khumairoh, Nur Sitti (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study examines the efficiency of cash management and its impact on the profitability of companies in Indonesia's retail trade sector. Using a qualitative approach, the research explores the practices and strategies employed by retail firms to manage cash flows effectively while maintaining operational stability and profitability. Data collection involves in-depth literature reviews and interviews with financial managers from select retail companies. The analysis focuses on identifying key challenges in cash management, including liquidity constraints, over-reliance on credit, and inefficiencies in cash conversion cycles. The findings reveal that efficient cash management significantly enhances profitability by reducing financial costs, optimizing working capital, and improving decision-making processes. Additionally, companies with robust cash management strategies are better equipped to adapt to market fluctuations and sustain long-term growth. The study underscores the importance of integrating technology, such as cash flow forecasting tools and automated payment systems, to streamline processes and mitigate risks. It concludes with actionable recommendations for retail companies, policymakers, and financial professionals to develop and implement more effective cash management practices. By contributing to the limited body of research on cash management in the retail trade sector in Indonesia, this study provides valuable insights for improving financial performance and fostering sustainable growth in a competitive business environment.